UPAYA PENINGKATAN MOTIVASI BELAJAR PKN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH SISWA KELAS VI SDN 015 PAGARAN TAPAH DARUSSALAM - Asma Nababan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low level of learning motivation among sixth-grade students at SDN 015 Pagaran Tapah Darussalam. The objective of the study was to improve students’ motivation in learning Civics through the implementation of cooperative learning using the Index Card Match type over a one-month period. The research was conducted at SDN 015 Pagaran Tapah Darussalam, involving 27 students of class VI. This study employed a classroom action research design and was carried out in March 2015. The research instruments included teacher and student activity observation sheets as well as learning achievement tests. Based on the analysis and discussion presented in Chapter IV, it can be concluded that the application of the cooperative learning method of the Index Card Match type effectively increased students’ motivation to learn Civics in class VI at SDN 015 Pagaran Tapah Darussalam. This improvement occurred because the use of the Index Card Match cooperative learning method encouraged higher student participation and created a more enjoyable learning atmosphere. The results showed that in the first cycle, the average learning motivation reached 68.5%, which increased significantly in the second cycle to an average of 84.6%, categorized as high. Under these conditions, student participation improved, which in turn contributed to a significant increase in learning motivation.